1994
DOI: 10.1172/jci117491
|View full text |Cite
|
Sign up to set email alerts
|

Sodium-dependent net urea transport in rat initial inner medullary collecting ducts.

Abstract: We reported that feeding rats 8% protein for 3 wk induces net urea transport and morphologic changes in initial inner medullary collecting ducts (IMCDs) which are not present in rats fed 18% protein. In this study, we measured net urea transport in microperfused initial IMCDs from rats fed 8% protein for -3 wk and tested the effect of inhibiting Na+/ K+-ATPase activity and found that adding 1 mM ouabain to the bath reversibly inhibited net urea transport from 14+3 to 6±2 pmol/mm per min (P < 0.01), and that re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(52 citation statements)
references
References 25 publications
0
52
0
Order By: Relevance
“…Schmidt-Nielsen and colleagues first demonstrated the existence of active urea reabsorption which is coupled to sodium reabsorption in the kidney of the spiny dogfish, Squalus acanthias (16). We showed that urea is actively reabsorbed via a secondary active, sodium-coupled cotransport process in the rat initial IMCD (IMCD 1 ) from rats fed a low-protein diet for 3 wk (9)(10)(11). We also showed that urea is actively secreted via a secondary active, sodium-coupled countertransport process in the deepest portion of the rat terminal IMCD, the IMCD 3 , but not in the middle third of the IMCD, the IMCD 2 , nor in the initial IMCD of rats fed a normal diet (12).…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…Schmidt-Nielsen and colleagues first demonstrated the existence of active urea reabsorption which is coupled to sodium reabsorption in the kidney of the spiny dogfish, Squalus acanthias (16). We showed that urea is actively reabsorbed via a secondary active, sodium-coupled cotransport process in the rat initial IMCD (IMCD 1 ) from rats fed a low-protein diet for 3 wk (9)(10)(11). We also showed that urea is actively secreted via a secondary active, sodium-coupled countertransport process in the deepest portion of the rat terminal IMCD, the IMCD 3 , but not in the middle third of the IMCD, the IMCD 2 , nor in the initial IMCD of rats fed a normal diet (12).…”
Section: Introductionmentioning
confidence: 94%
“…Tubules were transferred into a bath that was continuously exchanged and bubbled with 95% O 2 /5% CO 2 gas and perfused using standard techniques (10,12,20).…”
Section: Protocolsmentioning
confidence: 99%
See 1 more Smart Citation
“…The higher urea permeability in the adult BBMV could be due to maturational increases of other urea transporters such as the sodium-dependent urea transporter that has been recently described (14,15) . To assess the sodium dependence of urea transport in the proximal tubule apical membrane, urea uptake was measured in the presence and absence of a 20-mM sodium gradient in adult BBMV.…”
Section: Sodium Dependence Of Bbmv Urea Transportmentioning
confidence: 95%
“…UT-A) and secondary active Na + /urea counter-transport systems (Chou and Knepper, 1989;Isozaki et al, 1993;Isozaki et al, 1994a;Isozaki et al, 1994b;Sands et al, 1996;Kato and Sands, 1998a;Kato and Sands, 1998b), but not Na + /urea cotransporters, and because water with a salinity of 1 contained ~15mmoll -1 Na + , which was higher than the normal intracellular Na + concentration (10mmoll -1 ), the possibility of a Na + /urea counter-transporter being expressed in the apical membrane of the buccopharyngeal epithelial cells of P. sinensis cannot be eliminated at present. However, active buccopharyngeal urea excretion resulted in extraordinarily high urea concentrations (~614mmoll -1 ) in the saliva of turtles injected intraperitoneally with urea; therefore, the possibility of the presence of a novel active urea transporter independent of Na + movement in the apical surface of the buccopharyngeal epithelium cannot be ignored.…”
Section: The Buccopharyngeal Epithelium Is Capable Of Active Urea Excmentioning
confidence: 97%